2019
DOI: 10.3390/min9050325
|View full text |Cite
|
Sign up to set email alerts
|

LKZ-1: A New Zircon Working Standard for the In Situ Determination of U–Pb Age, O–Hf Isotopes, and Trace Element Composition

Abstract: This study introduces a new zircon reference material, LKZ-1, for the in situ U–Pb dating and O–Hf isotopic and trace element analyses. The secondary ion mass spectrometric analyses for this gem-quality single-crystal zircon yielded a weighted mean 206Pb/238U age of 572.6 ± 2.0 Ma (2σ, n = 22, MSWD = 0.90), with moderately high U concentrations (619 ± 21 ppm, 1 SD), restricted Th/U ratios (0.146 ± 0.002, 1 SD), and negligible common Pb content (206Pbc < 0.2%). A comparable 206Pb/238U age (570.0 ± 2.5 Ma, 2σ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 46 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…A suitable natural reference material should be homogeneous in both chemical and isotopic compositions at the scale of analysis. Previous studies have identified a number of natural zircons as reference materials suitable for geochronology and isotope geochemistry, including SL7 (Kinny et al ), CZ3 (Pidgeon et al ), SL13 (Claoué‐Long et al ), 91500 (Wiedenbeck et al ), Temora (Black et al ), BR266 (Stern ), GJ‐1 (Jackson et al , Morel et al ), Mud Tank (Woodhead and Hergt ), M257 (Nasdala et al ), Plešovice (Slama et al ), Sri Lanka (Gehrels et al ), OG1/OGC (Stern et al , Kemp et al ), Penglai (Li et al ), Qinghu (Li et al ), OD‐3 (Iwano et al ), M127 (Nasdala et al ), BB (Santos et al , Lana et al ), LGC‐1 (Tian et al ), GZ7/GZ8 (Nasdala et al ), LKZ‐1 (Cheong et al ) and GHR1 (Eddy et al ). However, most of them are either exhausted or have limited availability against the increasing demands of the microbeam laboratories.…”
mentioning
confidence: 99%
“…A suitable natural reference material should be homogeneous in both chemical and isotopic compositions at the scale of analysis. Previous studies have identified a number of natural zircons as reference materials suitable for geochronology and isotope geochemistry, including SL7 (Kinny et al ), CZ3 (Pidgeon et al ), SL13 (Claoué‐Long et al ), 91500 (Wiedenbeck et al ), Temora (Black et al ), BR266 (Stern ), GJ‐1 (Jackson et al , Morel et al ), Mud Tank (Woodhead and Hergt ), M257 (Nasdala et al ), Plešovice (Slama et al ), Sri Lanka (Gehrels et al ), OG1/OGC (Stern et al , Kemp et al ), Penglai (Li et al ), Qinghu (Li et al ), OD‐3 (Iwano et al ), M127 (Nasdala et al ), BB (Santos et al , Lana et al ), LGC‐1 (Tian et al ), GZ7/GZ8 (Nasdala et al ), LKZ‐1 (Cheong et al ) and GHR1 (Eddy et al ). However, most of them are either exhausted or have limited availability against the increasing demands of the microbeam laboratories.…”
mentioning
confidence: 99%
“…However, a matrix-matched reference material is necessary for accurate micro-beam isotope measurements to correct for instrument-induced mass bias and to assess external reproducibility. A number of natural zircons were identified as reference materials by previous number of natural zircons were identified as reference materials by previous studies, like SL7 [15], CZ3 [16], SL13 [17], 91500 [18], Temora [19], BR266 [20], GJ-1 [21,22], Mud Tank [23], M257 [24], Plešovice [25], Sri Lanka [26], OG1/OGC [27], Penglai [28], Qinghu [29], OD-3 [30], M127 [31], BB [32,33], LGC-1 [34], GZ7/GZ8 [35], LKZ-1 [36], GHR1 [37], and SA01 [38]. However, most of them are just used as a reference material for U-Pb geochronology, and the homogeneity of Li, O, and Hf isotopic compositions was not elaborately evaluated [15,17,26,30,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of them are just used as a reference material for U-Pb geochronology, and the homogeneity of Li, O, and Hf isotopic compositions was not elaborately evaluated [15,17,26,30,34,35]. Additionally, the availability of most of the natural zircon standards is limited [17,24,26,31,[34][35][36]. Among them, BB zircon, a newly developed zircon reference material from Sri Lanka, is potentially useful because of its abundance in quantity (~300g) [33].…”
Section: Introductionmentioning
confidence: 99%